Are We Spending Too Much on Print STEM Monographs? A Method and Analysis for Improving Monograph Allocations Based on Circulation Statistics. - Jonathan Nabe (Issues in Science and Technology Librarianship, 2013)
Circulation studies provide evidence of demand for monographs, but it is necessary to determine the goal of any analysis in order to select which statistics will be used. The goal of this analysis was to determine the appropriateness of expenditures on monographs within the STEM fields at Morris Library over a ten-year period. Percentage of unique title circulation and average circulation per title are best suited for this purpose. Results show variation among disciplines, but over-expenditure in all. Analysis of disciplines can aid in determining appropriate allocations for monographs, and analysis of subdisciplines can aid in targeting monograph acquisitions within any discipline. [ABSTRACT FROM AUTHOR]